Surrogate markers of intestinal dysfunction associated with survival in advanced cancers - Roxanne Birebent; Damien Drubay; Carolina Alves Costa Silva; Federica Marmorino; Giacomo Vitali; Gianmarco Piccinno; Yoan Hurtado; Adele Bonato; Lorenzo Belluomini; Meriem Messaoudene; Bertrand Routy; Marine Fidelle; et al. (OncoImmunology)
Deviations in the diversity and composition of the gut microbiota are called “gut dysbiosis”. They have been linked to various chronic diseases including cancers and resistance to immunotherapy. Stool shotgun based-metagenomics informs on the ecological composition of the gut microbiota and the prevalence of homeostatic bacteria such as Akkermansia muciniphila (Akk), while determination of the serum addressin MAdCAM-1 instructs on endothelial gut barrier dysfunction. Here we examined patient survival during chemo-immuno-therapy in 955 cancer patients across four independent cohorts of non-small cell lung (NSCLC), genitourinary (GU) and colorectal (CRC) cancers, according to hallmarks of gut dysbiosis. We show that Akk prevalence represents a stable and favorable phenotype in NSCLC and CRC cancer patients. Over-dominance of Akk above the healthy threshold was observed in dismal prognosis in NSCLC and GU and mirrored an immunosuppressive gut ecosystem and excessive intestinal epithelial exfoliation in NSCLC. In CRC, the combination of a lack of Akk and low sMAdCAM-1 levels identified a subset comprising 28% of patients with reduced survival, independent of the immunoscore. We conclude that gut dysbiosis hallmarks deserve integration within the diagnosis toolbox in oncological practice.